We have the following system of equations:
![\begin{gathered} x=-4\ldots(A) \\ 5x+4y=-16\ldots(B) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u61wwz5eyen9swizm5demoor9chkmkofgn.png)
Solving by substitution method.
If we substitute equation A into equation B, we get
![5(-4)+4y=-16](https://img.qammunity.org/2023/formulas/mathematics/college/ftk1g2mnewo9xgzzt2vzyp0g503lq11g0m.png)
since 5(-4)= -20, we have
![-20+4y=-16](https://img.qammunity.org/2023/formulas/mathematics/college/8erpdvpcyid3i41ornxnej1ljpdtibcb59.png)
If we move -20 to the right hand side as +20, we obtain
![\begin{gathered} 4y=-16+20 \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jvpb1iugxw2lwm9j2qq1dor8cg6972hkpt.png)
since -16+20=20-16 = 4, we get
![4y=4](https://img.qammunity.org/2023/formulas/mathematics/college/t1u3zdhiowyebj5362n8wx0xfit8kljyqt.png)
and finally, y is equal to
![\begin{gathered} y=(4)/(4) \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xdl6wvtreq2lepaoappbnq4v1dnlqi8e4i.png)
Since equation A tells us that x=-4, the solution of the system is
![\begin{gathered} x=-4 \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eawh40zlerjnir1cdcws8a6b3wcqrbc9ns.png)